An Italian interdisciplinary citizen observatory for the protection and promotion of night skies on year 12 of its evolution: challenges and opportunities from a Digital Earth perspective - Giacomelli, A; Maggi, E; Massetti, L (IOP conference series. Earth and environmental science, 2020)
Citizen observatories are community-based systems that can complement official networks for environmental data collection. This study proposes the case of a Citizen Observatory on light pollution, developed in Tuscany since 2008. Starting from the collection of measurement by volunteers, the observatory is now composed by a heterogeneous array of subjects (two research institutions, two rural communities, a rock-blues band, and a professional photographer) operating from local to international level through its connection with the international scientific community. This collaboration produced several outcomes: light pollution monitoring campaigns, numerous outreach events for raising citizen awareness on light pollution and its consequences and for the promotion of dark sky areas, input to global level position papers and scientific publications, the organization of an international Symposium on promotion and protection of the night sky.